Menumbuhkan Minat Belajar Bahasa Inggris Siswa Sekolah Dasar Melalui Metode ‘ESA’ - I Wayan Budiarta; Ni Wayan Kasni (Warmadewa Press, 2020)
Serangan Island now becomes the new emerging tourism area in Bali more specifically in Denpasar. The growth of tourism should be equivalent to the growth the society. Preparing qualified human resource is crucial especially the ability to speak a foreign language and one of the languages is English. Encouraging the interest of children especially the elementary students is a challenge that needs to be answered. This article is describing the exploration of seeking and determining appropriate method in teaching English for the students in order to improve the students’ interest in learning English as a second language as it was found that the students were not interested in learning English. This might because of poor students’ motivation and also it might be because of the less attractive method applied by the teacher in the process of learning English as students are easy to get bored. Based on that phenomenon this article tries to apply the method of ESA (Engage, Study, Activate) in teaching English for Elementary Student. The results show that the method is significantly changing the situation in the class when the students learning English. After applying the method significance change has occurred. The students have increased their motivation to study English as it can be seen from the activeness of the student in the process of learning. All students are enjoyed and involved in the class. Therefore it can be concluded that the method succeeds to be applied.